Investigating the Impact of Talent Management on the Retention of Human Resources: A Study in Zahedan Municipality - Kohestany, Zohreh; Yaghoubi, Nour Mohammad (International Review of Management and Marketing, 2017)
This study aimed to investigate the impact of talent management on the retention of human resource is in Zahedan Municipality. The research was descriptive-correlational and population consisted of all 100 employees in Zahedan Municipality. Talent management and retention of human resources questionnaires were used. Validity of questionnaires was confirmed by faculty professors and experts in Zahedan Municipality; their reliability obtained by Cronbach’s alpha coefficient was 95% and 93%, respectively. Regression test in spss16 software was used in order to data analysis. Test results showed that talent management effects on the retention of human resource. Moreover, all variables of social responsibility, employee pride, management support, performance management, intrinsic rewards, and health factors predict the retention of human resources. Keywords: talent management, retention of human resources, employees pride, turnover intention, satisfaction JEL Classification: M1